The role of customer expectations and competitive pressure in shaping firm innovation decisions towards sustainability: mediating effects of innovation perception - Thi Anh Phuong Tran (Cogent Business & Management)
This study aims to explore the innovation decision-making processes related to ‘green and sustainable development’ (GSD) in businesses, influenced by competitive pressure (CP) and customer expectations (CEs) through the process of innovation awareness. The study conducted an online survey (Google Forms) with the participation of 747 employees from different businesses in the Mekong Delta region. Through a deductive approach associated with positivist philosophy, the study evaluated the measurement and structural models using partial least squares structural equation modelling via the SmartPls software. The research results showed that CEs and CP positively impacted ‘innovation awareness’ (IA) and firm innovation decision-making (FID) in a green and sustainable direction via the mediating roles of perceived marketing innovation (PMI), perceived process innovation (PPI), and perceived organisational innovation (POI). As a result, this research has contributed significantly in terms of theory to research in this field and practice for the development of the Mekong Delta region.